Análise econômica da produção e comercialização de tomate na região do Médio Mearim e município de São Luis, Estado do Maranhão - Correia Filho, Francisco (1982)
The objective of this study was to determine and to analyse the structure of costs of production and purchasing of the tomato in the region of Middle Mearim and in Sao Luís, State of Maranhão. The data concerning to the production were gotten in the municipes of Dom Pedro and Presidente Dutra, in the region of Middle Mearim, the main region of tomato production in the State of Maranhão, in a period from August 1980 to July 1981. The allusive informations for the analysis of the variables of the costs of trade were colected in the region of Middle Mearim, through the local purchasers and at CEASA-MA and at the four higgest retailing markets of vegetables, fruit etc, in São Luís, the principal commercial center of these products in the State of Maranhão. These data are concerning to July 1981. The data used to determine and to analyse the anual margin of trade were gotten at the Service of Marketing Information of Maranhão and they are concerning to the period from August 1980 to July 1981. It was found that the average total cost of production is about Cr$ 269,45 per box of 25 kg. From this value, the fixed and variable costs represent 24,27% and 75,73%, respectively . The machines and equipaments are the principal itens included in the fixed costs, with 10,06% of average total cost. The labor and imputs are the variable costs with the highest participation in the average total cost of production, representing, respectively, 23,27% and 22,83%. It was found that the culture of tomatoes, in the region studied brought about economical profits, and that the costs, till a determinated point, decrease as soon as the production increases. The excellent production is about 1.814 boxes of 25 kg at a minimum average total cost of Cr$ 200,88 per box. About 93% of the productors produce less than this levei of production. The aggregate profit of retail and wholesale, the losses and carriage are the main variables of the cost of trade, respectively 40%, 28,85% and 17,07%. The average profit of the productor was about Cr$ 332,06 per box of 25 kg and its average participation in the price to the consumer was 51,44%, in a period from August 1980 to July 1981.